2017
DOI: 10.1111/apt.14101
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: repeat duodenal biopsy for patients with coeliac disease―physician heal thyself and dietitian heal the patient!

Abstract: Linked ContentThis article is linked to Pekki et al paper. To view this article visit https://doi.org/10.1111/apt.14048.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Although normalisation of coeliac specific serology usually occurs on a GFD, it has been demonstrated that negative TTA cannot be used as a reliable marker of histological healing (31,32) . Our results confirm the need to focus our attention onto good dietary instruction in order to improve GFD adherence and on the investigation of non-invasive strategies to assess adherence to a GFD (24)(25)(26)33,34) . We think that these alternative methods to identify dietary lapses, including urinary gluten peptides, may be particularly useful for patients who do not require an invasive follow-up (scenario 4) and those in whom a case-by-case evaluation is needed (scenario 3) (33) .…”
Section: Discussionsupporting
confidence: 76%
“…Although normalisation of coeliac specific serology usually occurs on a GFD, it has been demonstrated that negative TTA cannot be used as a reliable marker of histological healing (31,32) . Our results confirm the need to focus our attention onto good dietary instruction in order to improve GFD adherence and on the investigation of non-invasive strategies to assess adherence to a GFD (24)(25)(26)33,34) . We think that these alternative methods to identify dietary lapses, including urinary gluten peptides, may be particularly useful for patients who do not require an invasive follow-up (scenario 4) and those in whom a case-by-case evaluation is needed (scenario 3) (33) .…”
Section: Discussionsupporting
confidence: 76%